Examining Brain Based Learning Models Assisted Open-Ended Approach To Mathematics Understanding Concept - Suharja, Suharja; Mustadi, Ali; Oktari, Viscal (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
The implementation of this research is due to indications of learning problems related to students' difficulties in understanding mathematics in division material in third grade elementary school which results in students being weak in understanding mathematical concepts. This needs to be improved through the implementation of a brain-based learning model with an open-ended approach so that it affects students' understanding of mathematical concepts. Quasi-experiment with pretest posttest control group design was used as the basis for this research method. The study population consisted of 96 grade 3 students from 5 schools in cluster 5, Klaten. Simple randomization was used as a sampling technique with a sample of 48 students. The research instrument used was a test of 10 questions with essay type. Based on the results of the hypothesis test obtained at 0.018, the brain-based learning model assisted by an open-ended approach has an effect on students' understanding of mathematical concepts with an average increase of 34.96 seen from the pretest and posttest. This research contributes to influencing students' mathematical concept understanding ability in a more positive direction through collaboration between the brain-based learning model with an open-ended approach.